Peran Dan Tantangan Kekuasaan Kehakiman di Indonesia - Nazjwa Fatharani; Fikri Al -Zalmmi; Zaky Fauzi; Diandra Nazira Anshar (Lembaga Pengembangan Kinerja Dosen, 2024)
Law plays an important role in authority because it serves as a mechanism to legitimize public institutions and government institutions. Judicial power, which is part of state power, must have independence because only through independence can it control and limit legislative and executive power. In this case, independent judges can legally determine whether government actions to protect human rights are appropriate or not. This research uses normative juridical, which is an approach that focuses on legal provisions and legislation. This research approach uses analytical description to clarify the legal issues being discussed. This research uses primary data consisting of legal data in the form of judicial power legislation, coupled with secondary legal data in the form of books, journals, articles and others. The result of this research is that judicial power itself still has challenges that can occur, one of which is the intervention by internal and external judges themselves because of the elemental content of interests and power politics. Another factor is the poor and degraded morality of judges so that they can be bought and bribed by litigants, resulting in a decision that is not based on justice. This is certainly contrary to our constitution, namely the 1945 Constitution and the Constitution of the Republic of Indonesia.